2009
DOI: 10.1038/nature07681
|View full text |Cite
|
Sign up to set email alerts
|

A kiloparsec-scale hyper-starburst in a quasar host less than 1 gigayear after the Big Bang

Abstract: The host galaxy of the quasar SDSS J114816.64+525150.3 (at redshift z=6.42, when the Universe was <1 billion years old) has an infrared luminosity of 2.2×10 13 L 1,2 ⊙ , presumably significantly powered by a massive burst of star formation 3,4,5,6 . In local examples of extremely luminous galaxies such as Arp 220, the burst of star formation is concentrated in the relatively small central region of < 100 pc radius 7,8 . It is unknown on which scales stars are forming in active galaxies in the early Universe, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
287
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(335 citation statements)
references
References 29 publications
(44 reference statements)
45
287
2
1
Order By: Relevance
“…The CII line has been detected by Walter et al (2009), and the data are consistent with a 1kpc-scale starburst, of SF density 1000M /yr/kpc 2 . Surprisingly HCN has not been detected in this source, although HCN appears better correlated to star formation than CO (Gao & Solomon 2004).…”
Section: F Combessupporting
confidence: 57%
“…The CII line has been detected by Walter et al (2009), and the data are consistent with a 1kpc-scale starburst, of SF density 1000M /yr/kpc 2 . Surprisingly HCN has not been detected in this source, although HCN appears better correlated to star formation than CO (Gao & Solomon 2004).…”
Section: F Combessupporting
confidence: 57%
“…Under the assumption that the heating of the cold dust is dominated by young stars, the high FIR luminosity (L FIR ∼ 2 × 10 13 L , Beelen et al 2006) translates into a star-formation rate of ∼3000 M yr −1 . These high star-formation rates are corroborated by measurements of the [C ii] emission line at 158 μm (Maiolino et al 2005;Walter et al 2009). Mid-infrared observations Jiang et al 2006) show large amounts of hot dust near the ∼3 × 10 9 M black hole which accretes close to its Eddington limit (Willott et al 2003;Barth et al 2003).…”
Section: J1148+5251mentioning
confidence: 56%
“…Luminous quasar host galaxies (e.g. Maiolino et al, 2005;Iono et al, 2006;Maiolino et al, 2009;Walter et al, 2009;Wagg et al, 2010;Stacey et al, 2010;Gallerani et al, 2012;Carniani et al, 2013), SMGs (e.g. Ivison et al, 2010d;Stacey et al, 2010;Cox et al, 2011;De Breuck et al, 2011;Swinbank et al, 2012;Wagg et al, 2012;George et al, 2013;Huynh et al, 2013) and normal star-forming galaxies (e.g.…”
Section: Atomic Linesmentioning
confidence: 99%
“…The high-z data is subdivided into quasars and SMGs, and comes from Cox et al (2011) Willott et al (2013) A number of studies have used extremely high resolution [CII] observations to constrain the size of the emitting region of high-z quasar host galaxies. Walter et al (2009) derived a source size of ∼ 1.5 kpc, and suggested that the galaxy was undergoing an Eddington-limited starburst event. Similar compact sizes were derived for two z ∼ 4 quasar host galaxies by Gallerani et al (2012) and Carniani et al (2013), who also detected companion galaxies potentially due to merge with the quasar host.…”
Section: [Cii] Morphologies and Dynamicsmentioning
confidence: 99%